STRENGTHENING CHARACTER EDUCATION THROUGH HABITUATION ACTIVITIES - Aiman Faiz; Imas Kurniawaty; Purwati Purwati (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
Education is an important sector in the development of a nation, with quality education, the development of human resources will also be better. The purpose of this research is to describe the pattern of strengthening character education at SDN 2 Tukmudal. To achieve the research objectives, the research methodology uses a descriptive qualitative approach. The results of the study describe that strengthening character education at SDN 2 Tukmudal Sumber Cirebon with the let's reduce waste program is a form of instilling the value of caring for the environment. Not only that, in its implementation there is also a strengthening of the values of nationalism, religion, discipline and responsibility which are applied in habituation, learning and culturalization activities in SDN 2 Tukmudal. It is hoped that strengthening character education will produce graduates who have a strong character foundation as potential successors to the Indonesian nation.